Effects of mechanical and temporal parameters on tactile psychophysical responses - Yıldız, Mustafa Zahid. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2013., 2013)
Tactile feedback is becoming more important in clinical devices and engineering. Therefore, studies on basic sensory processing in the somatosensory system are essential. In this thesis, the mechanical and temporal parameters a ecting the absolute tactile detection threshold of human Pacinian (P) channel were investigated. Temporal summation in P channel was found to be independent of stimulus frequency and the experimental results did not t the classical model of temporal summation. The model needs to be modi ed to show the U-shaped Pacinian channel behavior. Additionally, the spatial summation property of the P channel was demonstrated on ngertip at three di erent contact locations and at three contactor sizes. The e ects of skin mechanics on psychophysical thresholds of the P channel were studied by measuring mechanical impedance. A signi cant correlation was found between the thresholds and the dynamic modulus of the skin. Conventionally, somatosensory evoked potentials (SEPs) are measured on the scalp by applying electrically stimulating the peripheral nerves in the clinical setting. Here, SEPs were represented by di erent types of wavelet functions, which can be used in data compression. Non invasive recordings of scalp potentials were also investigated by applying strong mechanical stimulation on the ngertip. However, time-frequency analysis did not show much useful information about stimulus properties, which would be useful in understanding basic somatosensory processes. The results of this thesis may be useful in various elds such as haptics, robotics, prostheses, dermatology, cosmetics. Speci cally, spatial and temporal summation should be incorporated in the high-frequency vibrotactile feedback in prosthetic arms.|Keywords : Touch, somatosensory, Pacinian channel, psychophysical threshold, temporal summation, spatial summation, skin mechanics, mechanical impedance, somatosensory evoked potentials.
Keywords: Touch.; Pacinian bodies.; Somatosensory evoked potentials.